Evidence of Weak Anderson Localization Revealed by the Resistivity, Transverse Magnetoresistance and Hall Effect Measured on Thin Cu Films Deposited on Mica - Oyarzun-Medina, S (Nature Research, 2021)
We report the resistivity of 5 Cu films approximately 65 nm thick, measured between 5 and 290 K, and the transverse magnetoresistance and Hall effect measured at temperatures 5 K < T < 50 K. The mean grain diameters are D = (8.9, 9.8, 20.2, 31.5, 34.7) nm, respectively. The magnetoresistance signal is positive in samples where D > L/2 (where L = 39 nm is the electron mean free path in the bulk at room temperature), and negative in samples where D < L/2. The sample where D = 20.2 nm exhibits a negative magnetoresistance at B < 2 Tesla and a positive magnetoresistance at B > 3 Tesla. A negative magnetoresistance in Cu films has been considered evidence of charge transport involving weak Anderson localization. These experiments reveal that electron scattering by disordered grain boundaries found along L leads to weak Anderson localization, confirming the localization phenomenon predicted by the quantum theory of resistivity of nanometric metallic connectors. Anderson localization becomes a severe obstacle for the successful development of the circuit miniaturization effort pursued by the electronic industry, for it leads to a steep rise in the resistivity of nanometric metallic connectors with decreasing wire dimensions (D < L/2) employed in the design of Integrated Circuits. © 2021, The Author(s).